2020
DOI: 10.1101/2020.01.08.898163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue engineered model of hepatic breast cancer micrometastasis shows host-dependent colonization patterns and drug responses

Abstract: Early stages of colonization of distant organs by metastatic cancer cells (micrometastasis) remain almost inaccessible to study due to lack of relevant experimental approaches. Here, we show the first 3D tissue engineered model of hepatic micrometastasis of triple negative breast cancer (TNBC). It reproduces characteristic histopathological features of the disease and reveals that metastatic TNBC cells colonize liver parenchymal and stromal extracellular matrix with different speed and by different strategies.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…These results are also in line with the observations from our previous study, where we investigated colonisation of the liver parenchymal and stromal compartments by MDA-MB-231 cells [ 26 ]. We showed that the cell growth and invasion patterns, as well as their morphology, critically depend on the stiffness of the ECM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are also in line with the observations from our previous study, where we investigated colonisation of the liver parenchymal and stromal compartments by MDA-MB-231 cells [ 26 ]. We showed that the cell growth and invasion patterns, as well as their morphology, critically depend on the stiffness of the ECM.…”
Section: Discussionsupporting
confidence: 92%
“…MDA-MB-231 cell line displaying a pronounced mesenchymal phenotype has been shown to form metastatic lesions in vivo [ 25 ]. We have found that the MDA-MB-231 colonisation patterns in whole-organ decellularized liver scaffolds varied dramatically across loose parenchymal (Young modulus, ~2 kPa) and denser (Young modulus, >2 kPa) stromal scaffold compartments [ 26 ], where cell morphology was one of the discriminants of the colonisation patterns. Cells infiltrated rapidly the parenchymal tissue, and their dominant morphological trait was identified as small round shape cells, whereas spindle-shaped, large-footprint cells were prevalent in the stromal compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, decellularized liver scaffolds have been manufactured by immersion decellularization of chick embryos, which bypasses the slow whole-organ decellularization approach. A dramatic reduction in doxorubicin efficiency against triple negative breast cancer liver metastases was demonstrated ( Guller et al, 2020 ). Importantly, the speed at which the matrices can be produced using this approach lends itself high throughput amenable for anticancer screening.…”
Section: Three-dimensional In Vitro and mentioning
confidence: 99%
“…Then the sterilization solution was removed, and the ALSs were washed with sterile PBS, placed in 24-well plates, and left under UV for 30 min, then the scaffolds were flipped upside down by Acellular liver scaffolds (ALSs) were prepared from chicken livers obtained from a local poultry supplier. The liver lobules were decellularized as described by us elsewhere with minor modifications [75,76]. Briefly, chicken liver lobules were washed with PBS and placed in 50-mL Falcon tubes, containing 35 mL of sodium dodecyl sulphate (0.1% v/v in water).…”
Section: Data Availability Statementmentioning
confidence: 99%